Masalah Pendidikan di Prancis Dalam Karya Rabelais, Montaigne dan Rousseau - Husen, Ida Sundari (UI Scholars Hub, 2002)
In the 16th., 17th. and 18th. century, the first ideas of educative reform in France appeared in litterary master pieces. Rabelais wrote his critics and proposals on child education in his stories Pantagruel (1532) and Gargantua (1534), developped later in the Essays (three volumes) written by Montaigne and in Rousseau’novel, Emile. Actually the same ideas were supported also by Descartes in Discours de la Méthode (1637) and Voltaire in L’Ingénu (1767). The central issue was the opposition between the old system of education focusing on learning by heart and theories and the system they proposed which gave importance on the formation of the way of thinking, in a pleasant learning atmosphere, in relation to real life and nature. Officially French education reform was started by the Minister of Education Jules Ferry in 1880 in the decrees proclaming compulsory education in the primary school, free of charge, and the separation between secular and religious education